Frequency and indications of elective and emergency cesarean sections in the Hospital Regional de Ayacucho, Peru - Pino-Anaya, Roaldo (2021)
Objective. To determine the frequency and indications of elective andemergency caesarean sections in relation to associated factors in the Hospital Regional de Ayacucho. Methods. A basic research of nonexperimental, descriptive, cross-sectional, prospective, correlational design with a quantitative approach was carried out, with a non-probabilistic and intentional sample of 94 post-cessation puerperal women, with prior informed consent. The survey technique was used for data collection, and the questionnaire and medical records were used as instruments to investigate the reason for cesarean section. In the inferential analysis, the chi-square test was used at 95 % confidence (p ≤ 0.05). Results. 51.8 % (1455) of deliveries were by cesarean section, the most frequent indications being previous cesarean section with 17.2 % of cases, cephalopelvic disproportion with 13.7 %, oligohydramnios with 11.3 % and others in lower percentages; likewise, 59.6 % of cesarean sections were emergency and 40.4 % elective. There is no significance p > 0.05 between cesarean sections and the factors parity, maternal age and socioeconomic status. Conclusions. The frequency of cesarean sections exceeds 50 %, with the first indications being previous cesarean section, cephalopelvic disproportion, oligohydramnios and acute fetal distress. The most common types of cesarean section are emergency and elective. There is no significance between cesarean sections and parity, maternal age and socioeconomic status.